Pashas : traders and travellers in the Islamic world - Mather, James; Yale University Press (New Haven : Yale University Press, 2009)
"Long before they came as occupiers, the British were drawn to the Middle East by the fabled riches of its trade and the enlightened tolerance of its people. The 'pashas' - merchants and travelers from Europe - discovered an Islamic world that was alluring, dynamic and diverse." "Ranging across two and a half centuries and through the great cities of Istanbul, Aleppo and Alexandria, James Mather tells the forgotten story of the men of the Levant Company who sought their fortunes in the Ottoman Empire. Their trade brought to the region not only merchants but ambassadors and envoys, pilgrims and chaplains, families and servants, aristocratic tourists and roving antiquarians. Together, their lives provide a fascinating insight into the meeting of East and West before the age of European imperialism."--BOOK JACKET.
-- Prologue: Jerusalem -- Aleppo -- Peace and trade -- Trading places -- People of the book -- Constantinople -- Galata -- Ambassadors -- Objects of enquiry -- Alexandria -- Antique lands -- The last pashas -- Epilogue: Crescent empire.
Includes bibliographical references and index.
Keywords: Company of Merchants of England Trading to the Levant -- History; British -- Travel -- Middle East -- History; Merchants -- Middle East -- History; Travelers -- Middle East -- History; Middle East -- Description and travel; Islamic countries -- Description and travel; Turkey, Eastern -- Description and travel; Middle East -- Relations -- Great Britain; Great Britain -- Relations -- Middle East; Turkey -- History -- Ottoman Empire, 1288-1918